2015
DOI: 10.3390/ijms160715287
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Molecular Design of Flutolanil Derivatives Targeted for Fumarate Respiration of Parasite Mitochondria

Abstract: Recent studies on the respiratory chain of Ascaris suum showed that the mitochondrial NADH-fumarate reductase system composed of complex I, rhodoquinone and complex II plays an important role in the anaerobic energy metabolism of adult A. suum. The system is the major pathway of energy metabolism for adaptation to a hypoxic environment not only in parasitic organisms, but also in some types of human cancer cells. Thus, enzymes of the pathway are potential targets for chemotherapy. We found that flutolanil is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 41 publications
(51 reference statements)
3
62
0
Order By: Relevance
“…(b) Structures representing MDH: 1BMD, in complex with NAD þ (40) , 2CMD, in complex with CIT (31) , 1B8U, in complex with NAD þ (43) , 1EMD, in complex with NAD þ and CIT (30) , 1Y7T, in complex with NADPH (74) , 1BDM, in complex with NAD þ (40) and 1IE3, in complex with NAD þ and PYR (6) . (c) Structures representing SDH: 1YQ3, in complex with FAD and UBQ (33) , 1NEK, in complex with FAD (84) , 1NEN, in complex with dinitrophenol-17 inhibitor ubiquinone binding site (84) , 4YXD, in complex with FTN (35) and 1ZOY, in complex with FAD and UBQ1 (71) .…”
Section: Molecular Docking Structural Analyses and Interaction Energmentioning
confidence: 99%
“…(b) Structures representing MDH: 1BMD, in complex with NAD þ (40) , 2CMD, in complex with CIT (31) , 1B8U, in complex with NAD þ (43) , 1EMD, in complex with NAD þ and CIT (30) , 1Y7T, in complex with NADPH (74) , 1BDM, in complex with NAD þ (40) and 1IE3, in complex with NAD þ and PYR (6) . (c) Structures representing SDH: 1YQ3, in complex with FAD and UBQ (33) , 1NEK, in complex with FAD (84) , 1NEN, in complex with dinitrophenol-17 inhibitor ubiquinone binding site (84) , 4YXD, in complex with FTN (35) and 1ZOY, in complex with FAD and UBQ1 (71) .…”
Section: Molecular Docking Structural Analyses and Interaction Energmentioning
confidence: 99%
“…suum is a suitable model for biochemical studies of mitochondrial NADH-fumarate reductase systems because the body sizes of adult worms are easy to manipulate. We previously reported that the NADH-fumarate reductase system is a good target for the development of novel, selective anthelmintic compounds as modeled in A. suum [38,39]. It is composed of complex I (NADH-quinone reductase, NQR), complex II (quinol-fumarate reductase, QFR), and a low-potential electron mediator, rhodoquinone (RQ).…”
Section: Nadh-fumarate Reductase System (Fumarate Respiration)mentioning
confidence: 99%
“…Flutolanil and atpenin A5 are known effective inhibitors of the quinone-binding site of A. suum complex II [42,43]. Elucidation of crystal structures of A. suum complex II in the presence of flutolanil provided useful information for the structure-based design of a more effective inhibitor [39,44]. As a crystallographic analysis of Echinococcus complex II is challenging, we conducted comparative analyses of E. multilocularis with other parasites and host enzymes.…”
Section: Echinococcosis 52mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported the crystal structures of TAO in complex with ascofuranone derivatives (3VVA and 3W54)[27] as well as A . suum QFR in complex with flutolanil (3VR9 and 3VRB)[28] , [29] , [30], its derivatives (4YSZ, 4YT0, 4YTM, 4YSX and 4YSY) and the substrate rhodoquinone (5C2T)[31], providing structural insights into their inhibition mechanisms. Both type of inhibitors bind to the quinol binding site of each target.…”
Section: Introductionmentioning
confidence: 99%